Analisis Tata Cara Pengelolaan Arsip Elektronik Dalam Manajemen Persuratan - Tengku Darmansyah; M Muflih Dermawan; Fachri Habib; Ahmad Rinaldi Siregar (CV. ITTC INDONESIA, 2024)
This research was conducted to answer how to analyze procedures for managing electronic records in correspondence management. The type of research used is library research or literature study, where researchers rely on various literature to obtain research data and use a qualitative approach because the data produced is in the form of words or descriptions. Electronic archives are a collection of information recorded using computer technology as electronic documents so that they can be viewed and reused, while electronic dynamic archives are dynamic archives that have an electronic or digital format, and require certain media according to the form of the archive to read them. Management of electronic records can be carried out in four cycles, namely: creation and storage, distribution and use, maintenance and disposition. Electronic archives can be archives created directly using electronic media or printed archives that are converted into digital archives.